REKAYASA ALAT PRES STEEL SHANK SEPATU DENGAN PENGGERAK SISTEM ULIR PADA PROSES PEMBUATAN SEPATU UNTUK INDUSTRI KECIL - Wawan Budi Setyawan (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2014)
Most shoes craftsmen are small and cottage industries who still working in a traditional way with limited capital. To assy shoes stiffener made of iron / shank on the soles, especially for shoes / footwear with relatively high heel are still beating it with a hammer to do for forming / bending of the reinforcing steel. This resulted in a relatively long process of attachment as to form a reinforcing steel follows the contour of the reference it self takes a long time. To overcome this then designed steel shank press machine that price is still affordable to the home craftsmen shoes / footwear. Therefore author conducted through a research design " SHANK STEEL PRESS TOOL ENGINEERING OF SHOES WITH SCREW DRIVE SYSTEM FOR SMALL INDUSTRIES ". This research was conducted with the aim to create a pressing machine steel shank with a screw system that adopt the principle of pressure that the system works to simplify the pressing mechanism that uses the engine manufacturer by comparing and combining the emphasis with a hammer. How it works to put pressure on the steel shank with a successor style screw system that will make the process of forming steel shank in the formation process easier and faster. The results showed the results of bending steel shank can be formed in an optimal and perfect, adjust the height of the right to be paired. The machine dimension are 40 cm x 25 cm x 50 cm, weight 25 Kg